2017
DOI: 10.4103/0972-9062.225838
|View full text |Cite
|
Sign up to set email alerts
|

Entomological determinants of malaria transmission in an epidemic prone area of District Nuh (Haryana state), India

Abstract: The results suggest that An. culicifacies (species A) is playing a major role in malaria transmission in the study area and is almost susceptible to deltamethrin. Timely two rounds of indoor residual spray of synthetic pyrethroid with proper dosage and good coverage would be helpful in reducing vector population and consequently the malaria incidence. In addition, personal protection measures by the community would supplement the major intervention tool (IRS) in decreasing the man-vector contact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
3
1
Order By: Relevance
“…fluviatilis , tested positive. An earlier study conducted in Nuh in 2015-2016 reported a sporozoite positivity rate of 0.26% [ 35 ], which is lower than the rate reported in this study (2.1%). The observed variability in the sporozoite rate could be attributed to differences in sample size, usage of LLINs, and malaria endemicity of the study sites.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…fluviatilis , tested positive. An earlier study conducted in Nuh in 2015-2016 reported a sporozoite positivity rate of 0.26% [ 35 ], which is lower than the rate reported in this study (2.1%). The observed variability in the sporozoite rate could be attributed to differences in sample size, usage of LLINs, and malaria endemicity of the study sites.…”
Section: Discussioncontrasting
confidence: 85%
“…culicifacies was previously reported in the Gadchiroli district of Maharashtra [ 32 , 33 ], Kalahandi, and 4 other districts in Odisha [ 34 ]. Furthermore, in Nuh, Haryana, possible resistance to deltamethrin was observed [ 35 ]. A multidistrict study conducted in 2009 on the susceptibility of An.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…culicifacies was found under the verification required category while An. stephensi was resistant to deltamethrin [ 23 ]. The findings of the current study showed that the frequency of resistance in both the malaria vectors is increasing in the study area.…”
Section: Discussionmentioning
confidence: 99%